Ketone body oxidation increases cardiac endothelial cell proliferation - Weis, Eva-Maria; Puchalska, Patrycja; Nelson, Alisa B; Taylor, Jacqueline; Moll, Iris; Safatul Hasan, Sana; Dewenter, Matthias; Hagenmüller, Marco; Fleming, Thomas; Poschet, Gernot; Hotz-Wagenblatt, Agnes; Backs, Johannes; et al. (EMBO molecular medicine, 2022)
Blood vessel formation is dependent on metabolic adaption in endothelial cells. Glucose and fatty acids are essential substrates for ATP and biomass production; however, the metabolism of other substrates remains poorly understood. Ketone bodies are important nutrients for cardiomyocytes during starvation or consumption of carbohydrate‐restrictive diets. This raises the question whether cardiac endothelial cells would not only transport ketone bodies but also consume some of these to achieve their metabolic needs. Here, we report that cardiac endothelial cells are able to oxidize ketone bodies and that this enhances cell proliferation, migration, and vessel sprouting. Mechanistically, this requires succinyl‐CoA:3‐oxoacid‐CoA transferase, a key enzyme of ketone body oxidation. Targeted metabolite profiling revealed that carbon from ketone bodies got incorporated into tricarboxylic acid cycle intermediates as well as other metabolites fueling biomass production. Elevation of ketone body levels by a high‐fat, low‐carbohydrate ketogenic diet transiently increased endothelial cell proliferation in mouse hearts. Notably, in a mouse model of heart hypertrophy, ketogenic diet prevented blood vessel rarefication. This suggests a potential beneficial role of dietary intervention in heart diseases.
Online veröffentlicht: 18 February 2022
Gesehen am 26.03.2024